Perceived exertion, postural control, and muscle recruitment in three different quadruped exercises performed by healthy women - Clemente, Patrícia Cardoso; de Almeida, Luane Landim; Vicente, Eduardo José Danza; Fonseca, Diogo Simões; Souza, Victor Hugo; Felício, Diogo Carvalho; Garcia, Marco Antonio Cavalcanti (Frontiers in Physiology, 2022)
Although quadruped exercises (QE) have been a part of rehabilitation and sports programs, there is no clarity on how these exercises challenge the musculoskeletal system. Therefore, this cross-sectional study investigated the perceived exertion, postural demands, and muscle recruitment profiles imposed by three QE postures. Surface electromyographic (sEMG) signals were recorded from transverse abdominis, longissimus dorsi, multifidus, and iliocostalis lumborum from 30 sedentary healthy women, bilaterally. They performed the classic quadruped exercise (CQ), a variation with shoulder flexion (FQ), and the homolateral quadruped (HQ). Borg scores (BS) and the center of pressure (CoP) from the palmar statokinesiogram were also recorded. Surface EMG signals were normalized using the myoelectric activity recorded from two other postures while performing isometric voluntary contractions (IVC). Results were analyzed using one- (CoP) and three-way (sEMG data) ANOVA with Bonferroni post hoc tests (α = 0.05). The Borg scale was analyzed using the Friedman test. The CQ provided lower BS and CoP than HQ (p < 0.05), followed by a higher sEMG activity (~51% of IVC) than FQ (~47% of IVC; p = 0.53) and HQ (~44% of IVC; p = 0.01). In turn, HQ provided greater BS (p > 0.05) than CQ and FQ. The results suggested that the HQ was the most challenging exercise regarding CoP and BS, although CQ presented a higher symmetrical sEMG activity. Since QE are often prescribed in exercise programs, specific knowledge of the characteristics of each QE makes prescribing safer and more efficient.